2015
DOI: 10.3109/1547691x.2015.1017060
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to DDT metabolitep,p′-DDE increases autoimmune type 1 diabetes incidence in NOD mouse model

Abstract: The incidence of autoimmune Type 1 diabetes (T1D) has been steadily rising in developed countries. Although the exact cause of T1D remains elusive, it is known that both genetics and environmental factors play a role in its immunopathogenesis. Whereas a positive association between p,p 0 -DDE, a DDT metabolite, and Type 2 diabetes (T2D) has been well established, its role in T1D development in an experimental animal model has never been elucidated. This study seeks to investigate the effects of DDE exposure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Furthermore, higher plasma levels of POPs and higher plasma inflammatory cytokine concentrations were found in First Nations individuals compared to Caucasians from Canada [102]. Moreover, acute exposure to DDE, increased T cell proliferation as well as Th1-dependent inflammatory cytokines and Cox2 while chronic exposure decreased suppressive regulatory T cells as well as protective suppressive cytokines [103,104].…”
Section: Pro-inflammatory Properties Of Popsmentioning
confidence: 93%
“…Furthermore, higher plasma levels of POPs and higher plasma inflammatory cytokine concentrations were found in First Nations individuals compared to Caucasians from Canada [102]. Moreover, acute exposure to DDE, increased T cell proliferation as well as Th1-dependent inflammatory cytokines and Cox2 while chronic exposure decreased suppressive regulatory T cells as well as protective suppressive cytokines [103,104].…”
Section: Pro-inflammatory Properties Of Popsmentioning
confidence: 93%
“…Finally, a nested case-control study by Rignell-Hydbom et al (2010) investigated the role of PCB-153 and DDE in T1D; the authors concluded that these compounds did not exhibit negative effects on T1D development, even suggesting that they might impart a possible (although not significant) protection. Interestingly, Cetkovic-Cvrlje et al (2015) recently showed that DDE was able to accelerate T1D development in NOD mice treated chronically with the compound.…”
Section: Discussionmentioning
confidence: 98%
“…NOD mice were used following an experimental design previously used to study DDE effects on T1D development in the same model (Cetkovic-Cvrlje et al 2015). Initially, PCB-153 effects on development and severity of diabetes during subchronic exposures had been studied using NOD females, whereas the mechanism of action in the context of pollutant influence on the immune system, particularly T-cells, was evaluated using NOD males and females.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations